PEMBERDAYAAN MASYARAKAT KELURAHAN SULAMADAHA DENGAN PELATIHAN PEMBUATAN KAPSUL DAUN KELOR UNTUK MENINGKATKAN KUALITAS KESEHATAN MASYARAKAT - Amran Nur; Ismail Rahman (Universitas Mataram, 2023)
Moringa (Moringa oleifera) is a type of tropical plant that is easy to cultivate because it does not require intensive care and has high drought tolerance. In addition, various parts of the Moringa plant contain good nutrition and are widely used in various fields such as: food, health, beauty and the environment, so it is very natural to get the nickname Tree For Life. The purpose of this activity is to provide information regarding the various benefits of the Moringa plant which can be optimized, especially in terms of health. One way to use Moringa leaves is to make preparations that are more practical so that people can easily consume them, these preparations can be in the form of Moringa leaf capsules. This activity was carried out using a group approach method in the form of socialization to community groups in the Sulamadaha village. The socialization explained the main benefits of Moringa leaves and then showed how to make Moringa leaf capsules and explained the advantages of using Moringa leaf capsules which are more practical to use without reducing the benefits of the Moringa leaves themselves. The implementation of this counseling activity went smoothly and was attended by the community enthusiastically, seen by the community's participation with question and answer activities regarding the benefits and advantages of the preparation if it is made into Moringa leaf capsules. The results of this activity further opened up the people of Sulamadaha Village about the benefits of Moringa leaves, especially for health and provided an understanding that Moringa preparations are not only made in the form of vegetables but can be made in a more practical form, namely with capsule preparations. And in the end the people of the Sulamadaha village after this activity have received information and have understood the processing of Moringa leaves into preparations that are far more practical without eliminating the main benefits of the Moringa leaves themselves.